Improving Body Mechanics Using Experiential Learning and Ergonomic Tools in Massage Therapy Education - Anderson, BA, LMT, BCTMB, CEAS, Robin B. (International Journal of Therapeutic Massage & Bodywork, 2018)
Introduction: Current industry data suggest that the rise in occupational injuries for massage therapists is contributing to a significant number leaving the profession after a few short years. While many massage therapists are taught meth-ods for proper body mechanics and self-care within their career educational programs, there are few consistencies in the theoretical approaches to these concepts, even though it is a required component in massage therapy career training. Purpose: This study demonstrates a measurable and effective teaching method using a combination of experiential and transformative learning theory models and authentic ergonomics measurement tools to teach effective body mechanics in entry level career training that may be sustainable for new massage therapists entering the field. Methods: Four cohorts of students (N = 17) enrolled in a kinesiology course for massage thera-pists were studied using a mixed-methods time series experimental design. A pre- and post-test was conducted by utilizing two industry standard ergo-nomics risk factor assessment tools as measurable data for score comparison, to denote improvements in each student’s risk factor tendencies and provide evidentiary support of learning transfer. Between the pre- and post-test, students participated in a series of experiential learning exercises within class sessions during the semester and completed two reflection journals discussing their experiences. Results: The results showed that there was a statistically significant reduction in ergonomics risk factor scores for all students studied. Conclusion: The success of this study demon-strates that the instructional design using expe-riential and transformative educational theory and general ergonomics concepts is an effective approach to teaching proper body mechanics to massage therapy students which can be adopted into universally accepted curriculum on many levels and could eventually contribute to reduction of occupational injury in the future.